(untitled) (Bioresearch Communications, 2021)
Parents of children with developmental disabilities, particularly Autism Spectrum disorder, are known to be at risk for high levels of psychological distress. The present study aimed to adapt the Quality of Life in Autism Questionnaire (QoLA, parent-version) in the context of Bangladeshi culture. The sample included 50 participants. Participants were selected from the Institute of Paediatric Neurology and Autism (IPNA, BSMMU) and some special schools of Dhaka city. World Health Organization’s (WHO, 2009) guidelines were followed in translating the QoLA and adaptation for use in Bangladesh. For the parent-report version of the QoLA, Cronbach’s coefficients were 0.880 and 0.725 for part A and part B subscale items, respectively. The Pearson correlation coefficients for the test-retest reliability were r =0.964 for part A of the scale and r = 0.954 for part B. These psychometric properties are comparable to those obtained in the initial QoLA validation study (Eapen et al. 2014). Results of this study demonstrate that the Bangla version of the QoLA (Parent version) provides a valid measure of quality of life and is suitable for use in Bangladesh. Bioresearch Commu. 7(1): 960-966, 2021 (January